Physical fitness and activity level in Norwegian adults with achondroplasia. Issue 4 (31st December 2020) - de Vries, Olga Marieke; Johansen, Heidi; Fredwall, Svein Otto
Abstract: This cross‐sectional Physical Fitness Study compared cardiorespiratory fitness (VO2 peak), six‐minute walk test (6MWT), muscle strength (30sSTS), balance (BESS), and self‐reported physical activity level (IPAQ) in Norwegian adults with achondroplasia (ACH) to reference values of average‐statured individuals. The feasibility of the physical fitness tests and IPAQ was explored. Forty‐three adults (22 women) participated. Mean age was 38 years (range 16–69 years). Mean differences (95% CI) for men and women with ACH compared to reference values were: VO2 peak. −7.0 m/min/kg (−13.6 to −0.5, p = .037), and − 7.9 ml/kg/min (−11.6 to −4.3, p < .001); 6MWT −270.8 m (−340.4 to −201.2, p < .001), and − 196.7 m (−244.3 to −149.0, p = .001); 30sSTS ‐4.6 repetitions (−7.8 to −1.5, p = .006), and − 1.1 repetitions (−3.4 to 1.1, p = .335). There were no differences within ACH participants, except for VO2 peak, where men performed better. Sufficient physical activity (> 600 metabolic equivalent of task weekly) was achieved by 79% of the participants. The feasibility of the 6MWT and 30sSTS was good. There was a strong correlation between the VO2 peak and 6MWT (men: r = 0.63, p = .007; women: r = 0.71, p < .001). The findings indicate that the 6MWT and 30sSTS test are useful in assessing functional exercise capacity and muscle strength in adults with ACH.